Simulation of Wide Area Network for Multiple Offices Connectivity Using Enhanced Interior Gateway Routing Protocol (EIGRP) - Amanze, BC; Nwoke , BC; Agoha , UK (International Journal of Computer Sciences and Engineering, 2019)
Wide Area Network (WAN) is a critical important functionality of modern businesses because latency, jitter and packet loss associated with WAN often causes performance of applications to degrade, the outage of WAN link often causes one or more sites to be offline and the lead time to either install a new WAN link or to increase the capacity of existing WAN link can be quite lengthy. This paper focuses on the summary of the key components of some of the emerging approaches to WAN architecture and design and concludes with a call to action that outlines a project plan that network organizations can use to evolve their WAN. The motivation for this paper is to reduce the cost of transmission lines and equipment and improve network performance and response time. The approach taken in the design is based on approaching the high availability service problem from three perspectives; network resiliency, device resiliency and operational resiliency. Top down methodology which considers requirement analysis before technology selection is used. Packet tracer and operating Cisco IOS software are the design tools employed in the implementation of this paper.